Hand bone densitometry: a more sensitive standard for the assessment of early bone damage in rheumatoid arthritis. Issue 11 (9th May 2007) - Haugeberg, Glenn; Green, Michael J; Conaghan, Philip G; Quinn, Mark; Wakefield, Richard; Proudman, Susanna M; Stewart, Sheena; Hensor, Elizabeth; Emery, Paul
Abstract : Objective: To examine the role of hand dual-energy x ray absorptiometry (DEXA) compared with radiography in the assessment of bone involvement in patients with early rheumatoid arthritis (RA) who have active disease. Methods: The study population (n = 79) had RA of <12 months' duration and were selected for poor prognostic features. Clinical data and bone mineral density (BMD) data were collected at baseline, 24 and 48 weeks. Hand radiographs were performed at baseline and 48 weeks. Bone damage analyses were performed for the group and individuals using the smallest detectable change (SDC) method. Results: At baseline, mean disease duration was 8.5 months, erythrocyte sedimentation rate was 34.3 mm/hour, C-reactive protein was 40.2 mg/l, Health Assessment Questionnaire score was 1.35 and 81% of patients were positive for rheumatoid factor. Mean (95% CI) hand BMD loss was 2.5% (−3.5 to −1.5) at 24 weeks and 2.6% (−3.8 to −1.5) at 48 weeks. Individual hand bone loss exceeding the SDC was seen in 46.8% at 24 weeks and in 58.2% at 48 weeks. In the subgroup of 58 patients who had undergone radiography, radiographic joint damage score evaluated by the Sharp–van der Heijde method increased from 4.8 to 10.6 (p = 0.001). Individual hand bone loss in this subgroup exceeding the SDC was seen in 50.0% at 24 weeks and in 56.9% at 48 weeks, whereas at 48 weeks only 22.4% had deteriorated in modified Sharp score. Conclusion: The study results indicate that hand DEXA is a more sensitive tool than radiology (radiographic joint-damage scores), for measuring disease-related bone damage in early RA.